RoadDamageVision: Annotated Dataset of Road Damage Images - Luis Augusto Silva Zendron; Valderi Leithardt (2026)
This dataset was developed under the hypothesis that deep learning and computer vision techniques can be effectively used to detect and classify various types of road surface defects from drone-based visual data. By providing annotated images captured in different countries and environments using aerial platforms, the RoadDamageVision dataset supports the development of scalable, low-cost, and automated road monitoring systems.